Pragmatic approaches for addressing alcohol in general practice: Development of a tailored implementation intervention - Potthoff, Sebastian; O'Donnell, Amy Jane; Karlsen, Andrea Taksdal; Brendryen, Håvar; Lid, Torgeir Gilje (Frontiers in Health Services, 2022)
Introduction: Alcohol consumption is a leading global risk factor for ill-health and premature death. Alcohol screening and brief intervention (SBI) delivered in primary care is effective at reducing alcohol consumption, but routine implementation remains problematic. Screening all patients for excessive drinking (universal screening) is resource-intensive and may be at odds with general practitioners’ (GPs’) perceived professional role. This study aimed to develop a tailored, theory-based training intervention to strengthen GPs’ ability to address alcohol and to manage alcohol-related health problems through a pragmatic approach based on clinical relevance. Methods: A qualitative study design involving focus group interviews and a structured questionnaire for free text replies with GPs in Norway. Behavioural analysis assessed factors influencing delivery of SBI according to the ‘capability, opportunity, motivation and behaviour’ (COM-B) model to inform intervention development using the Behaviour Change Wheel. Qualitative data were analysed using framework analysis and an iterative approach was adopted to develop the training. Results: A purposive sample of GPs attended the focus groups (n=25) and completed the questionnaire (n=55). Four areas required additional support including: understanding the link between alcohol use and health problems; opening up the conversation on alcohol use; addressing alcohol and dealing with obstacles; and following-up and maintaining change. Findings informed the development of a four-session interactive training intervention and a digital intervention for providing support for patients between consultations to address the identified needs. Conclusion: This work highlights the value of pragmatic, relevance-based clinical strategies, as opposed to universal screening approaches to addressing alcohol in primary care. A pragmatic approach is more in line with GPs existing clinical skill set and holds the potential to improve widespread uptake and implementation of SBI in routine primary care.